2015
DOI: 10.1055/s-0034-1544002
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant Platelets and the Pathways Leading to Cell Death

Abstract: Platelets are critical mediators of thrombosis and hemostasis. In response to agonist, platelets aggregate to form a thrombus via ligand binding of the glycoprotein IIb/IIIa receptor. However, activated platelets are heterogeneous in nature and a subset of platelets stimulated by strong agonists support the assembly of the coagulation complexes. It is proposed that these "procoagulant" platelets have a unique role in hemostasis and thrombosis as the link between primary and secondary hemostasis, localizing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The reduction in PAC-1 binding found on PS-positive platelets has been reported previously and has been described as a down-regulation of the fibrinogen receptor 40 . However, it was recently suggested that this interpretation might need to be revisited 41 , as PS-positive, PAC-1-negative platelets may still bind another conformation-specific antibody, LIBS-6, that also recognize α IIb β 3 when bound to fibrinogen 42 . As PAC-1 has higher affinity for active α IIb β 3 than fibrinogen 14 , 42 and was present during the 10 min activation, PAC-1 should have been able to bind a number of α IIb β 3 receptors whenever these became active.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in PAC-1 binding found on PS-positive platelets has been reported previously and has been described as a down-regulation of the fibrinogen receptor 40 . However, it was recently suggested that this interpretation might need to be revisited 41 , as PS-positive, PAC-1-negative platelets may still bind another conformation-specific antibody, LIBS-6, that also recognize α IIb β 3 when bound to fibrinogen 42 . As PAC-1 has higher affinity for active α IIb β 3 than fibrinogen 14 , 42 and was present during the 10 min activation, PAC-1 should have been able to bind a number of α IIb β 3 receptors whenever these became active.…”
Section: Discussionmentioning
confidence: 99%
“…The distinct morphology of procoagulant platelets has led to the terminology of blebbing, balloon(ing), or balloon-like platelets (31)(32)(33)(34)(35). Procoagulant platelets have also been referred to as SCIP (sustained calcium-induced platelet morphology) platelets (36), necrotic/4-[N-(S-glutathionylacetyl)amino]phenylarsonous acid (GSAO)-binding platelets (37)(38)(39), superactivated platelets (40), capped platelets (21,41), and zombie platelets (42). Agbani and Poole (43) recently proposed "procoagulant platelets" as the unifying term for this activated platelet subpopulation.…”
Section: Procoagulant Phosphatidylserine-exposing Platelet Subpopulatmentioning
confidence: 99%
“…Furthermore, annexin V is potentially function blocking, which may be a confounder within a flow cytometry based or in vivo experimental methods. 125 Notwithstanding the lack of a universally accepted, sensitive and specific assay for this platelet subset, suitable for whole blood application, several studies, albeit from a single research group, have demonstrated potential utility of the procoagulant platelet subset as a biomarker in CVD. Patients with a higher level of procoagulant platelets following a largeartery stroke had a higher risk of stroke recurrence.…”
Section: Procoagulant Plateletsmentioning
confidence: 99%